Theoretical studies of perfluorochemicals (PFCs) adsorption mechanism on the carbonaceous surface. (November 2019) - Li, Mu; Sun, Feiyun; Shang, Wentao; Zhang, Xiaolei; Dong, Wenyi; Liu, Tongzhou; Pang, Wen
Abstract: Understanding the mechanism by which perfluorochemicals (PFCs) adsorbed on carbonaceous surface is eventually important to the design and process optimization of effective PFCs removal technologies. In this study, the possible binding mechanism of six different PFCs onto carbonaceous surface was investigated by means of first principles quantum mechanical methods based on density functional theory (DFT) calculation and wave function analysis. The adsorption process fitted well with pseudo-second-order kinetic indicated that chemical bonding could not be underestimated. The results indicate that there were monolayer adsorption, electrostatic and hydrophobic interactions existed in PFCs adsorption process. DFT results suggested that the adsorption of PFCs on carbonaceous surface was one chemisorption process that accompanied by Van der Waals interactions. As there was different head functional groups in PFOS and PFOA, their adsorption capacity mainly controlled by the availability of active sites that was occupied by PFCs. The variation of chain length of PFBS and PFOS also take a certain responsible for different adsorption paths, due mainly to their hydrophobic effect. The obtained results from wave function and DFT analysis give in-depth understanding of PFCs adsorption on carbonaceous surface and help to their effectively removal. Highlights: Binding mechanism of PFCs onto PAC was studied by using DFT. PFCs adsorption involves electrostatic and hydrophobic interactions. Chain length of PFBS and PFOS impacts on adsorption paths.